Elaboration and Physico-Chemical Characterization of the Gibbsite Li(OH)3 Hybrid Material - Belkham, N. el H.; Benachour, D.; Mehamha, A. (Engineering, Technology & Applied Science Research, 2021)
A hybrid material can be defined as a combination of two components of different chemical nature. The combination of a mineral matrix and organic matter has multiple significance. From a chemical point of view, it allows the obtaining of bi-functional materials that combine the chemical properties of their components. The development of new materials with specific properties and nanostructured Lamellar Double Hydroxides (LDHs) has been widely investigated due to their great importance. This study focuses on the development of a hybrid material consisting of a matrix of alumina trihydrate Al(OH)3 (gibbsite). Previous studies on the synthesis of suspension LDHs by lithium salts intercalation in a gibbsite matrix were examined, while the obtained samples were characterized by different physicochemical methods.